Dynamic structural and microstructural responses of a metal–organic framework type material to carbon dioxide under dual gas flow and supercritical conditions. Issue 1 (29th January 2023) - Allen, Andrew J.; Cockayne, Eric; Wong-Ng, Winnie; Culp, Jeffrey T.; Kuzmenko, Ivan
Abstract : The structural and microstructural responses of a model metal–organic framework material, Ni(3‐methyl‐4, 4′‐bipyridine)[Ni(CN)4 ] (Ni‐BpyMe or PICNIC‐21), to carbon dioxide sorption are measured, in situ, using small‐angle X‐ray scattering and X‐ray diffraction under both dual gas flow and supercritical CO2 pressure conditions. Experimental results are compared with density functional theory predictions aimed at providing insights concerning how such materials can be designed or modified to optimize the desired gas sorption properties. Abstract : The structural and microstructural responses of a model metal–organic framework material, Ni(3‐methyl‐4, 4′‐bipyridine)[Ni(CN)4 ] (Ni‐BpyMe or PICNIC‐21), to CO2 adsorption and desorption are reported for in situ small‐angle X‐ray scattering and X‐ray diffraction measurements under different gas pressure conditions for two technologically important cases. These conditions are single or dual gas flow (CO2 with N2, CH4 or H2 at sub‐critical CO2 partial pressures and ambient temperatures) and supercritical CO2 (with static pressures and temperatures adjusted to explore the gas, liquid and supercritical fluid regimes on the CO2 phase diagram). The experimental results are compared with density functional theory calculations that seek to predict where CO2 and other gas molecules are accommodated within the sorbent structure as a function of gas pressure conditions, and hence the degree of swelling and contraction in the associated structure spacings and void spaces. These predictions illustrate the insights that can be gained concerning how such sorbents can be designed or modified to optimize the desired gas sorption properties relevant to enhanced gas recovery or to addressing carbon dioxide reduction through carbon mitigation, or even direct air capture of CO2 .